Glofitamab in relapsed/refractory diffuse large B-cell lymphoma: Real-world data - TOPTAŞ, TAYFUR (My University, 2023)
Glofitamab is a CD3xCD20 bi-specific antibody with two fragments directed to the CD20 antigen and a single CD3-binding fragment. Encouraging response and survival rates were recently reported in a pivotal phase II expansion trial conducted in patients with relapsed/refractory (R/R) B-cell lymphoma. However, the real-world data of patients of all ages with no strict selection criteria are still lacking. Herein, this retrospective study aimed to evaluate the outcomes of diffuse large B-cell lymphoma (DLBCL) patients who received glofitamab via compassionate use in Turkey. Forty-three patients from 20 centers who received at least one dose of the treatment were included in this study. The median age was 54 years. The median number of previous therapies was 4, and 23 patients were refractory to first-line treatment. Twenty patients had previously undergone autologous stem cell transplantation. The median follow-up time was 5.7 months. In efficacy-evaluable patients, 21% and 16% of them achieved complete response and partial response, respectively. The median response duration was 6.3 months. The median progression-free survival (PFS) and overall survival (OS) was 3.3 and 8.8 months, respectively. None of the treatment-responsive patients progressed during the study period, and their estimated 1-year PFS and OS rate was 83%. The most frequently reported toxicity was hematological toxicity. Sixteen patients survived, while 27 died at the time of the analysis. The most common cause of death was disease progression. One patient died of cytokine release syndrome during the first cycle after receiving the first dose of glofitamab. Meanwhile, two patients died due to glofitamab-related febrile neutropenia. This is the largest real-world study on the effectiveness and toxicity of glofitamab treatment in R/R DLBCL patients. The median OS of 9 months seems promising in this heavily pretreated group. The toxicity related mortality rates were the primary concerns in this study.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Oncology; Health Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); HEMATOLOJİ; ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); HEMATOLOGY; bispecific antibodies; glofitamab; relapsed; refractory diffuse large B-cell lymphoma; SINGLE-ARM; MULTICENTER